Exploring The Cultural Tapestry Of Tanjung Balai:Unveiling Culinary Lexicon Through Ecolinguistics And Cognitive Anthropology - Mery Silalahi (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2024)
This study aims to elucidate the cultural significance embedded within the culinary lexicon of the Tanjung Balai community. Leveraging the frameworks of ecolinguistics and cognitive anthropology, this research interprets the cultural values inherent in culinary lexicon. Through analysis, it was deduced that the Tanjung Balai culinary culture embodies multifaceted functions, encompassing cultural, social, and health dimensions. The cultural function serves to delineate the identity and distinctiveness of the community. Socially, it fosters notions of camaraderie, familial bonds, neighborhood cohesion, industriousness, environmental stewardship, etiquette, resilience, optimism, collaborative spirit, and unity. Additionally, the health function ascribes medicinal properties to ingredients, believed to promote well-being such as lactation, cardiovascular health, and overall bodily wellness. Furthermore, these culinary elements are purported to remedy various ailments including stomach ailments, cholesterol issues, stiffness, dental discomfort, and asthma.